Artefacto de estimulación cognitiva para las funciones de la atención y memoria en pacientes con Alzheimer en fases leves. (2021)
Alzheimer's is an incurable, terminal and progressive disease, it is expected that in 2030, 10% of the elderly will suffer from this disease, that is, around 65.7 million people in the world.